과학교과에 대한 학생들의 흥미도 실태 조사 - 김상달; 이상균; 최성봉; Kim, Sang-Dal; Lee, Sang-Gyun; Choi, Sung-Bong (대한지구과학교육학회지, 2010)
Students' emotional attitude not only affects their achievement in a meaningful way but also is an important educational goal in its own right. This research investigated how students' interest in science varies among elementary, middle and high-school students based on a survey and reviews of previous research results. We analyzed students learning attitude in terms of interest in and enjoyment of science, instrumental motivation in science, science learning anxiety, and self-concept in science. Major findings are students showed more negative attitudes in intrinsic motivation, instrumental motivation, value perception of science, and confidence in science as they move in to a higher school level. According to students' explanation, science classes got bored in a higher grade because of difficult contents, lack of experiments and activities, and teachers' monotonous explanations. Based on the results, recommendations on how to improve students' attitudes towards science are suggested. First of all we need to secure more science instructional hours in the school curriculum than the 7th national curriculum to implement improved science teaching and learning methods.